2017
DOI: 10.1002/vnl.21592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of analcime zeolite synthesized from local pottery stone as nucleating agent on crystallization behaviors and mechanical properties of isotactic polypropylene

Abstract: This study reported the synthesis of analcime zeolite (AN‐zeolite) from a local pottery stone via hydrothermal method using 2 M NaOH at 120°C for 8 h in a Teflon‐lined stainless steel autoclave. The as‐synthesized AN‐zeolite was characterized for its phase composition, morphology, and particle size using X‐ray diffraction (XRD) analysis, scanning electron microscopy, and dynamic light scattering analysis, respectively. Subsequently, the AN‐zeolite was used as a nucleating agent for isotactic polypropylene (iPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Figure 1 shows the WAXD profiles of neat PP and nucleated PPs with different content of nucleating agent, and the main crystal parameters d and Litalichkl and crystallinity (Xc,XRD) were listed in Table 2 according to Equation () and (). Six characteristic peaks indicating the existence of α phase at 2 θ of 14.1, 16.9, 18.6, 21.1, 21.9, and 25.6° for all samples which were assigned to the crystal planes of (1 1 0), (0 4 0), (1 3 0), (1 1 1), (1 3 1), and (0 6 0), respectively 36–38 . And one distinct peak at 2 θ of 16.1° was observed in both PP and PP‐0.1 NA, showing the presence of (3 0 0) lattice plane of the β phase.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Figure 1 shows the WAXD profiles of neat PP and nucleated PPs with different content of nucleating agent, and the main crystal parameters d and Litalichkl and crystallinity (Xc,XRD) were listed in Table 2 according to Equation () and (). Six characteristic peaks indicating the existence of α phase at 2 θ of 14.1, 16.9, 18.6, 21.1, 21.9, and 25.6° for all samples which were assigned to the crystal planes of (1 1 0), (0 4 0), (1 3 0), (1 1 1), (1 3 1), and (0 6 0), respectively 36–38 . And one distinct peak at 2 θ of 16.1° was observed in both PP and PP‐0.1 NA, showing the presence of (3 0 0) lattice plane of the β phase.…”
Section: Resultsmentioning
confidence: 87%
“…However, Balkaev et al 23 prepared calcium stearate/PP composites and found the tensile strength decreased from 32.2 to 29.3 MPa when calcium stearate as a nucleating agent reached the content of 0.25 phr. And Chuayjuljit et al 38 also found the elongation at break of analcime zeolite/PP composites reduced from 12.4% to 6.6% when analcime zeolite as the nucleating agent gets the content of 0.5 phr. Based on the respective analysis in the literature, the above reversed tendencies compared to Table 6 were mainly caused by the worse dispersion of the nucleating agent, which was controlled well in this work.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to the conventional applications, PP can also be widely employed as fibers and engineering plastics due to its excellent balance of mechanical, thermal, chemical, and electrical properties. The major users of PP are related to the packaging industries, household appliances, electrical devices, automotive industries, ropes, upholsteries, constructions, etc., because PP has several beneficial and desirable properties, such as light weight, good stiffness, high tensile and flexural strength, good chemical, fatigue, thermal and electrical resistances, easy processability, and recyclability [1][2][3][4][5][6][7]. Nevertheless, PP has been found to suffer from some shortcomings, including poor toughness and notched impact resistance especially at low temperature, which may be due to its relatively high glass transition temperature (Tg ~ -10℃ to 0℃) and crystallized ability that generally forms large spherulites, leading to the presence of voids at the spherulite boundaries and the reduction in its toughness and impact resistance [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the consumption of PP over the years has been very high and continuously increased, mainly owing to a large variety of available added fillers, and the steady improvement of its property profiles in all fields (academia and industry) [11]. Use of inorganic mineral fillers for preparing polymer composites is a straightforward and convenient method for reducing the cost of plastic products and also improving some properties of polymers, especially mechanical and thermal properties, such as tensile strength, stiffness, tear strength, abrasion resistance, heat distortion temperature (HDT), flame retardancy, and thermal stability [2,6,7,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%